America's water : federal roles and responsibilities - Rogers, Peter P., 1937- (Twentieth Century Fund Book Ser., 1993)
Were water considered an industry, it would be one of the largest in the United States, surely the most capital-intensive, and the most closely regulated by Congress. Yet as Peter Rogers argues in this readable, pragmatic, and scientifically grounded assessment of national water issues, it would also be one of the most fragmented and least coherent areas of public policy. Rogers brings together all aspects of water (and water use) to look at policy formation from technical, economic, and political points of view. He shows why these separate perspectives must be considered simultaneously if intelligent policies are to be developed to protect this indispensable resource for present and future generations. Although water use has declined since 1980, the U.S. still consumes more than twice as much water per capita as any other country in the world. Weighing current resources against future demand, Rogers covers a host of complex water issues facing a thirsty, affluent nation. He explains why the federal role needs to be developed and clarified in a number of areas - from changing the unrealistic expectations of the American public for clean water at any cost to financing the rebuilding of infrastructure that is nearly a century old, from reforming intergovernmental relations and the committee structure in Congress to preserving and restoring wetlands and developing a national drought management policy. Of the two basic approaches to policy formation - spelling out desirable norms and attempting to achieve them, or building pragmatically on what has been feasible in the past - Rogers advocates the feasibility approach. The challenge, he asserts, is to develop a federal policy that will reform the historical patchwork of state-state and state-federal agreements and allow them to work together without abrupt dislocations.